2014
DOI: 10.21109/kesmas.v0i0.378
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Touch dan Nyeri Pasca Pembedahan

Abstract: Penanganan nyeri pada pasien yang dilakukan oleh profesi perawat lebih banyak mengacu pada pendekatan terapi medis dan farmakologis. Penelitian ini bertujuan untuk mengetahui pengaruh therapeutic touch terhadap nyeri pasien pasca operasi. Penelitian ini menggunakan desain kuasi eksperimental yang dilakukan pada 60 orang responden, terdiri dari 30 orang kelompok intervensi dengan therapeutic touch dan 30 orang kelompok kontrol dengan teknik napas dalam. Penelitian berlangsung di ruang rawat bedah pasien dewasa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Alp and Yucel 41 studied 60 women (TT, 30; control, 30) living in nursing homes and found that TT reduced the women's anxiety levels and increased their comfort levels. In a literature review investigating the effects of TT in cancer patients, it was suggested that TT reduced pain, anxiety, and fatigue; positively affected mood; provided relaxation; increased vitality; and raised life satisfaction 14 . These results showed that TT, which has no adverse effects and can be applied virtually anywhere and anytime, supports the body's natural healing process by repairing the imbalance in energy flow, thus reducing the severity of menopausal complaints and increasing the quality of life of women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alp and Yucel 41 studied 60 women (TT, 30; control, 30) living in nursing homes and found that TT reduced the women's anxiety levels and increased their comfort levels. In a literature review investigating the effects of TT in cancer patients, it was suggested that TT reduced pain, anxiety, and fatigue; positively affected mood; provided relaxation; increased vitality; and raised life satisfaction 14 . These results showed that TT, which has no adverse effects and can be applied virtually anywhere and anytime, supports the body's natural healing process by repairing the imbalance in energy flow, thus reducing the severity of menopausal complaints and increasing the quality of life of women.…”
Section: Discussionmentioning
confidence: 99%
“…TT, which is among the CAM methods with increasing use in recent years, is a modern-age interpretation of an ancient healing experience 12 . TT is a noninvasive nursing intervention that directs life energy to patients and balances it, and the flow of energy increases the overall energy, removes blockages, and creates an environment that promotes the acceleration of the natural healing process to alleviate ailments or symptoms caused by imbalances and blockages in life energy fields 13,14 . The North American Nursing Diagnosis Association has recognized “energy field disorder” as a nursing diagnosis 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Terdapat jurnal serupa tentang menurunan nyeri menggunakan Therapeutic touch. Penelitian Mumpuni (2014) tentang Therapeutic touch dan operative pain mendapatkan hasil data rata-rata skala nyeri pasien sebelum dilakukan terapi adalah 5,27 dan rata-rata skala nyeri pasien sesudah dilakukan tindakan terapi adalah 2,43. Rata-rata penurunan nyeri responden adalah 2,83 (Mumpuni, 2014).…”
Section: Abstrakunclassified
“…Penelitian Mumpuni (2014) tentang Therapeutic touch dan operative pain mendapatkan hasil data rata-rata skala nyeri pasien sebelum dilakukan terapi adalah 5,27 dan rata-rata skala nyeri pasien sesudah dilakukan tindakan terapi adalah 2,43. Rata-rata penurunan nyeri responden adalah 2,83 (Mumpuni, 2014). Intervensi pada penerapan ini adalah melakukan observasi dari pemberian self healing terhadap penurunan skala nyeri pada pasien post operasi.…”
Section: Abstrakunclassified